Effect of STN/GPi DBS on swallowing function in Parkinson's disease as assessed by Video fluoroscopy: A retrospective study. (October 2022) - Henry, Katharine A.; Singh, Rohin; Zhang, Nan; Lyons, Mark K.; McNett, Karen; Neal, Matthew T.; Mehta, Shyamal H.
Abstract: Introduction: The goal of the study is to objectively assess changes in swallowing (using "gold standard" video fluoroscopy (VFS)) following Deep Brain Stimulation (DBS) surgery in Parkinson's disease (PD) patients. There are few studies on the effect of DBS on swallowing in PD. We use VFS to assess swallowing function pre- and post-DBS. Methods: Our study participants underwent pre- and post-DBS VFS (6 months later) in the practically defined on state. We converted VFS reports into an objective numerical scale. Higher scores denote more severe dysphagia. We used non-parametric test (Wilcoxon signed rank test) to test if the difference between pre- and post-DBS swallow score is significantly different from 0. Results: Fifty-four PD patients completed pre- and post-DBS evaluations. Twenty-five patients had bilateral GPi DBS (46.3%) and 29 had bilateral STN DBS (53.7%). The mean (SD) post-DBS swallow score is 1.9 (2.0) and pre-DBS swallow score is 1.6 (1.3). The difference is not significantly different from 0 (p = 0.16). In our study, swallow scores for majority of the patients (39 out of 54) did not change after DBS regardless of lead location. Six (11.1%) PD patients had post-DBS swallow score decrease on average by 1 (SD: 0) points. 9 (16.7%) patients had post-DBS swallow score increase on average by 2.7 (SD: 2.3) points. Conclusion: There was no statistically significant change in the swallow scores pre-and 6 months post-DBS with VFS when assessed in the practically defined on state, regardless of the site of bilateral lead implantation. Hence, we believe that DBS does not improve or reduce swallow function in a clinically meaningful way in PD. Highlights: Largest study of video flouroscopic swallowing assessment of PD patients pre & post DBS. Both STN and GPi DBS patients assessed. Neither STN nor GPi DBS changed swallowing in a clinically meaningful way in PD. Trend to more improvement in swallowing post DBS in GPi group than STN group.